Multiple Light-Activated Photodynamic Therapy of Tetraphenylethylene Derivative with AIE Characteristics for Hepatocellular Carcinoma via Dual-Organelles Targeting - Chuxing Chai; Tao Zhou; Jianfang Zhu; Yong Tang; Jun Xiong; Xiaobo Min; Qi Qin; Min Li; Na Zhao; Chidan Wan (Pharmaceutics, 2022)
Photodynamic therapy (PDT) has emerged as a promising locoregional therapy of hepatocellular carcinoma (HCC). The utilization of luminogens with aggregation-induced emission (AIE) characteristics provides a new opportunity to design functional photosensitizers (PS). PSs targeting the critical organelles that are susceptible to reactive oxygen species damage is a promising strategy to enhance the effectiveness of PDT. In this paper, a new PS, 1-[2-hydroxyethyl]-4-[4-(1,2,2-triphenylvinyl)styryl]pyridinium bromide (TPE-Py-OH) of tetraphenylethylene derivative with AIE feature was designed and synthesized for PDT. The TPE-Py-OH can not only simultaneously target lipid droplets and mitochondria, but also stay in cells for a long period (more than 7 days). Taking advantage of the long retention ability of TPE-Py-OH in tumor, the PDT effect of TPE-Py-OH can be activated through multiple irradiations after one injection, which provides a specific multiple light-activated PDT effect. We believe that this AIE-active PS will be promising for the tracking and photodynamic ablation of HCC with sustained effectiveness.